Study of Some Reproductive Traits in Mabuya multifasciata (Sauria: Scincidae) Regarding Sexual Dimorphism during 2013-2015 - Hazarika, Moushumi; Sharma, D.K (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The Mabuya skink is a widely distributed species in India as well as in North East India and China (Zhaao and Adler, 1995; Ngnyen et al., 2009). In fact the species Mabuya multifasciata is commonly found in the open region of villages, secondary forests of different humid regions and in the region with variable temperatures (Ngnyen et al. 2009; Li et al. 2010). Many reptiles lay eggs while Mabuya gives birth to live young. This is a unique feature in case of lizards and skink as for example Mabuya multifasciata. We studied the size of the eggs and the nutrients and its effect on the reproductive cycle. The male reproductive cycle was also studied.